'Navigation for an ocean of interminable scepticism' revisited: John Henry Newman and the place of theology in the university. Issue 3 (2nd October 2021) - Morgan, Stephen
ABSTRACT: The place of theology is under threat in the modern university. It is denied a place, except insofar as it is useful in the training of religious professionals or as a phenomenon in its own right, on the grounds that relate to an unscientific scientism that both makes metaphysical assumptions it itself does not recognise as scientific or denies its own epistemological commitments. This article argues that the notion of education in 'liberal knowledge' or 'universal knowledge', the idea at the heart of John Henry Newman's The Idea of a University provides a sufficiently robust counter to these assaults on the place of theology proper in the modern university and that refusing such a place to it undermines the claim of universities to use the name at all. It is precisely the uselessness of theology that guarantees its place in the university committed to universal knowledge and universal enquiry.